2016
DOI: 10.1038/ni.3631
|View full text |Cite
|
Sign up to set email alerts
|

A cycle of Zap70 kinase activation and release from the TCR amplifies and disperses antigenic stimuli

Abstract: Cell-surface-receptor pathways amplify weak, rare and local stimuli to induce cellular responses. This task is accomplished despite signaling components that segregate into nanometer-scale membrane domains. Here we describe a ‘catch-and-release’ mechanism that amplified and dispersed stimuli by releasing activated kinases from receptors lacking intrinsic catalytic activity. Specifically, we discovered a cycle of recruitment, activation and release for Zap70 kinases at phosphorylated T cell antigen receptors (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(109 citation statements)
references
References 54 publications
2
107
0
Order By: Relevance
“…The CD3ε immunoreceptor tyrosine‐based activation motif (ITAM), however, was already found phosphorylated in ex vivo isolated, non‐stimulated Treg cells. Hence it is fair to speculate that the signal amplification mechanism involving the dissociation of ZAP70 from the TCR complex, as very recently described for Tconv cells , is already induced in non‐stimulated Treg cells. This would support ZAP70 function in inside‐out signalling and adhesion of Treg cells, which did not require its kinase activity .…”
Section: Discussionmentioning
confidence: 72%
“…The CD3ε immunoreceptor tyrosine‐based activation motif (ITAM), however, was already found phosphorylated in ex vivo isolated, non‐stimulated Treg cells. Hence it is fair to speculate that the signal amplification mechanism involving the dissociation of ZAP70 from the TCR complex, as very recently described for Tconv cells , is already induced in non‐stimulated Treg cells. This would support ZAP70 function in inside‐out signalling and adhesion of Treg cells, which did not require its kinase activity .…”
Section: Discussionmentioning
confidence: 72%
“…When bound to the TCR, ZAP‐70 can be activated to phosphorylate downstream targets that ultimately lead to T cell activation. Therefore, a single TCR/pMHC‐binding event can potentially be translated into the activation of multiple ZAP‐70 molecules . This signaling may also be sustained beyond pMHC binding because it has been suggested that, upon internalization, TCRs may continue to signal within the T cell .…”
Section: Mechanisms Of T‐cell Sensitivity To Antigenmentioning
confidence: 99%
“…By comparing the different ITAMs among the CD3 subunits (CD3 ζ , CD3 δ , CD3 ε and CD3 γ ), it is likely that ZAP‐70 preferentially binds to fully phosphorylated CD3 ζ . Recently, a ‘catch‐and‐release’ model for ZAP‐70 activation has been proposed by Katz et al . After recruitment of ZAP‐70 to the phosphorylated TCR–CD3 complexes and ZAP‐70 phosphorylation by Lck, activated ZAP‐70 is released from the TCR–CD3 complexes into the plane of the plasma membrane.…”
Section: Zap‐70mentioning
confidence: 99%
“…Consequently, empty phospho‐TCR–CD3 complexes allow the recruitment of additional ZAP‐70 molecules to the TCR–CD3 for activation of additional ZAP‐70. The released ZAP‐70 translocates within the membrane into adjacent protein islands to mediate phosphorylation of its substrates including the linker for the activation of T cells (LAT) and the SH2‐domain‐containing leucocyte protein of 76 000 MW (SLP‐76) . Phosphorylated LAT and SLP‐76 adaptor proteins have various interacting partners such as the phospholipase C‐γ1, which is recruited to these two proteins to form the LAT/SLP‐76 signalosome .…”
Section: Zap‐70mentioning
confidence: 99%
See 1 more Smart Citation